2022
DOI: 10.1186/s12284-022-00580-6
|View full text |Cite
|
Sign up to set email alerts
|

The Methylation Inhibitor 5-Aza-2′-Deoxycytidine Induces Genome-Wide Hypomethylation in Rice

Abstract: DNA methylation is a conserved epigenetic modification which is vital for regulating gene expression and maintaining genome stability in both mammals and plants. Homozygous mutation of rice methyltransferase 1 (met1) gene can cause host death in rice, making it difficult to obtain plant material needed for hypomethylation research. To circumvent this challenge, the methylation inhibitor, 5-Aza-2′-deoxycytidine (AzaD), is used as a cytosine nucleoside analogue to reduce genome wide hypomethylation and is widely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In this study, four concentrations of 5-Aza-dC, 5 μM, 10 μM, 20 μM and 30 μM, were tested in a pretest study according to previous studies [ 61 , 62 ], and 20 μM of 5-Aza-dC was selected for treatment. While most of the previous studies were conducted by applying 5-Aza-dC in the culture medium to study the effect of DNA methylation on the growth and development of plant tissues and organs [ 48 , 60 ], in the present study, we sprayed the leaves directly with 5-Aza-dC and found the optimal concentration to promote the development of cucumber fruits. One of the reasons that 5-Aza-dC promotes fruit enlargement may be that 5-Aza-dC treatment alters the gene expression of C5-MTase and dMTase, thereby altering the DNA methylation level of genes associated with sink-source carbon partitioning to facilitate assimilate loading.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, four concentrations of 5-Aza-dC, 5 μM, 10 μM, 20 μM and 30 μM, were tested in a pretest study according to previous studies [ 61 , 62 ], and 20 μM of 5-Aza-dC was selected for treatment. While most of the previous studies were conducted by applying 5-Aza-dC in the culture medium to study the effect of DNA methylation on the growth and development of plant tissues and organs [ 48 , 60 ], in the present study, we sprayed the leaves directly with 5-Aza-dC and found the optimal concentration to promote the development of cucumber fruits. One of the reasons that 5-Aza-dC promotes fruit enlargement may be that 5-Aza-dC treatment alters the gene expression of C5-MTase and dMTase, thereby altering the DNA methylation level of genes associated with sink-source carbon partitioning to facilitate assimilate loading.…”
Section: Discussionmentioning
confidence: 94%
“…However, high concentrations of methylation inhibitors can lead to the yellowing and even death of plant organs [ 54 , 55 , 56 ]. Previous studies have shown that DNA methylation inhibitors in a certain concentration range can change DNA methylation levels and promote gene expression after treating rice, Arabidopsis , Salvia miltiorrhiza and strawberry [ 57 , 58 , 59 , 60 ]. In this study, four concentrations of 5-Aza-dC, 5 μM, 10 μM, 20 μM and 30 μM, were tested in a pretest study according to previous studies [ 61 , 62 ], and 20 μM of 5-Aza-dC was selected for treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To test this, we used the methylation inhibitor 5-azacytidine (5-AZA) to partially cripple DNA methylation in seedlings, so that we could examine the effect of mbd2 in this sensitized background. 5-AZA reduces DNA methylation genome-wide by covalently linking to DNA methyltransferases and inhibiting their activity 3334 . We treated Col-0 and mbd2 seedlings with 100uM of 5-AZA and performed WGBS to examine the extent of demethylation.…”
Section: Figmentioning
confidence: 99%
“…5‐aza and hydroxyurea were used as hypo‐ or hyper‐methylating agents to study the relationship between SL and DNA methylation in a parasitic plant branched broomrape ( Phelipanche ramosa ) (Lechat et al, 2015). Liu et al (2022) examined the effects of 5‐aza‐2’‐deoxycytidine (AzaD) as a methylation inhibitor in rice and found that AzaD‐treated seedlings display similar CG hypomethylation and distribution with that of osmet1‐2 mutant. Interestingly, the application of 5‐aza increased the contents of tanshinones in Chinese sage ( Salvia miltiorrhiza ) (Yang et al, 2022a), highlighting the potential of using CREs in Chinese medicine to improve the contents of effective components.…”
Section: Chemical Genetics and Its Application To Epigenetics Studiesmentioning
confidence: 99%